The Power and the Glorification Papal Pretensions and the Art of Propaganda in the Fifteenth and Sixteenth Centuries - de Jong, Jan L. (Penn State University Press, 2015)
Focusing on a turbulent time in the history of the Roman Catholic Church, The Power and the Glorification considers how, in the fifteenth and sixteenth centuries, the papacy employed the visual arts to help reinforce Catholic power structures. All means of propaganda were deployed to counter the papacy's eroding authority in the wake of the Great Schism of 1378 and in response to the upheaval surrounding the Protestant Reformation a century later. In the Vatican and elsewhere in Rome, extensive decorative cycles were commissioned to represent the strength of the church and historical justifications for its supreme authority. Replicating the contemporary viewer's experience is central to De Jong's approach, and he encourages readers to consider the works through fifteenth- and sixteenth-century eyes. De Jong argues that most visitors would only have had a limited knowledge of the historical events represented in these works, and they would likely have accepted (or been intended to accept) what they saw at face value. With that end in mind, the painters' advisors did their best to "manipulate" the viewer accordingly, and De Jong discusses their strategies and methods